Analysis of Student Needs for Video Media Materials for Cooperative Learning Models in Biology Learning Strategy and Design Courses - Nadira Hannifa; Diana Susanti; Liza Yulia Sari (Journal Of Biology Education Research (JBER), 2022)
In the process of the Biology Learning Strategy and Design course at the Biology Education Study Program, PGRI University of West Sumatra with the material of cooperative learning models, lecturers use learning media, one of which is video media sourced from youtube. The purpose of this research is to find out how much students need for cooperative learning model video media in the Biology Learning Strategy and Design course. The research was designed with a 4D development model and only at the Define stage, namely the analysis of student needs. The results of the analysis of student needs showed  in the category of very need. This means that there is a need for the development of video media on cooperative learning model materials. Based on the results of the study, it can be concluded that the students' need for video media for cooperative learning model materials is good to develop.